Prangos munzurensis (Apiaceae), a new species from East Anatolia, Turkey - Lyskov, Dmitry; Duran, Ahmet; Yavuz Paksoy, Mehmet; Samigullin, Tahir (Phytotaxa, 2022)
A new species, Prangos munzurensis (Apiaceae), is described and illustrated from Tunceli Province, Eastern Turkey. The new species is related to Prangos heyniae, P. abieticola, and P. denticulata and differs from them in the number of rays, length of bracts, indumentum of petals, ultimate segments of leaves, stylopodium features, fruit morphology and anatomy, and distributional range. It also differs from P. ferulacea in presence of furrows between blocks of inner mesocarp, number of umbel rays, and puberulous petals. A comprehensive description of the morphological and carpo-anatomical features, photographs, and data on the geographical distribution, habitat and ecology, and conservation status are also provided. In addition, P. munzurensis is recognized as a separate species by molecular analysis of nrITS/ETS.